2014
DOI: 10.1136/bmjopen-2014-005183
|View full text |Cite
|
Sign up to set email alerts
|

Parental separation and behaviours that influence the health of infants aged 7–11 months: a cross-sectional study

Abstract: ObjectiveAnalyse the parental behaviours that are recognised as influencing the health of very young children based on family structure (parents separated or not).DesignCross-sectional study.SettingFree preventive medicine consultations in the French Community of Belgium.ParticipantsExamination of 79 701 infants aged 7–11 months as part of a free preventive medicine consultation. The data came from an assessment conducted 7–11 months after birth during which information was collected, namely about the parents’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
1
8
0
1
Order By: Relevance
“…This is far from being negligible for a relatively commonplace situation. These observations are similar to those made in a cross-sectional study that analysed a large sample of Belgian infants aged 7 to 11 months: [19] between 2010 and 2012, exposure to smoking was more frequent in children when the parents were separated, with an OR of 1.5 (95% CI 1.3–1.7) adjusting for the mother’s age, occupation, and level of education. That confirms what has been said by Belgian GPs, who indeed offered an explanation for their observations: that separated parents exhibited more risky behaviours, including smoking, because of their anxiety [18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is far from being negligible for a relatively commonplace situation. These observations are similar to those made in a cross-sectional study that analysed a large sample of Belgian infants aged 7 to 11 months: [19] between 2010 and 2012, exposure to smoking was more frequent in children when the parents were separated, with an OR of 1.5 (95% CI 1.3–1.7) adjusting for the mother’s age, occupation, and level of education. That confirms what has been said by Belgian GPs, who indeed offered an explanation for their observations: that separated parents exhibited more risky behaviours, including smoking, because of their anxiety [18].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, our study shows that when parents are separated, parental behaviour is significantly poorer concerning the health of children aged under 3 years (passive smoking, oral hygiene and amblyopic screening) regardless of the level of maternal education or cultural environment. These results are echoed in other studies, which also show a greater risk of exposure to smoking, suboptimal nutrition and lower adherence to the immunisation schedule when infants did not live with two parents who were together [19]. In the event of parental separation, family doctors or paediatricians should be more focused on parental behaviour that may affect the health of their children such as interruption of contraception, pregnancy plans and/or postnatal follow-up.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Third, a strong increase in participation was observed for children who grow up in one-parent families. There is some evidence that single parents have an increased risk of non-participation in preventive child health examinations [ 27 , 28 ] and incomplete immunisation schedules [ 29 , 30 ]. One hypothesis is the time limit of single parents [ 28 , 30 ] and the increase after implementation of the reminder system could be explained by the fact that the examination was simply forgotten.…”
Section: Discussionmentioning
confidence: 99%
“…Yet other studies, some prospective in nature [ 32 ], have demonstrated the positive impact of breastfeeding for at least 6 months on the psychomotor development of children during the first 5 years of life. Other studies have revealed a relationship between maternal marital status and breastfeeding [ 33 ], in particular including a cross-sectional study demonstrating a significant association between parental separation and specific parental behaviors, such as less frequent breastfeeding or earlier weaning [ 34 ]. This relationship between breastfeeding and the child’s development could at least be partly accounted for by the regulation mechanisms of cortisol metabolism and stress in children [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%